Prawo dowodowe w amerykańskim procesie karnym : aresztowanie i zatrzymanie osoby - Głowacka, Aleksandra (Koło Naukowe Doktryn Politycznych i Prawnych, Katedra Doktryn Politycznych i Prawnych, Wydział Prawa, Administracji i Ekonomii Uniwersytet Wrocławski, 2016)
The author of this paper discusses the issue of arrest and detention of person in the US criminal procedure, including the reasons of using these measures. The paper concerns institutions are unfamiliar to Polish law, such as citizen’s arrest or bail bondsman. Development also applies to the problem using weapons by US police, criticized recently practice of stop and frisk, as well as the controversial system of bail. Due to the nature of American law, the author quoted various lawsuits (for example United States v. Salerno), which have contributed to consolidating the practice of justice
Keywords: areszt; zatrzymanie osoby